Staphylococcus epidermidis ST2 strains associated with bloodstream infections contain a unique mobile genetic element encoding a plasmin inhibitor - Amy A. Gomez; Clara Kjerfve; Minseo Choi; Wen Liu; Kelly Churion; Sheila Thomas; Holger Rohde; Sam Shelburne; Jon T. Skare; Magnus Hook; Srishtee Arora (mBio, 2024)
ABSTRACT Staphylococcus epidermidis, a common commensal bacterium, is a leading cause of nosocomial catheter-associated bloodstream infections. S. epidermidis sequence type 2 (ST2) is specifically recognized globally for causing invasive disease. In this study, we identified a novel putative integrated conjugative element, pICE-Sepi-ST2, unique to the genomes of S. epidermidis ST2. Our investigation identified pICE-Sepi-ST2 in all ST2 isolates from bloodstream infections. Meanwhile, ST2 isolates from other infection sources, such as catheters, prosthetic joints, and fracture fixations, showed variable pICE-Sepi-ST2 prevalence. pICE-Sepi-ST2 encodes two putative cell wall anchored proteins that we have designated SesX and SesY. Biochemical characterization of SesY revealed that it binds both plasminogen (Plg) and plasmin (Pln) and inhibits Pln’s ability to cleave a chromogenic substrate and degrade fibrin clots. Furthermore, all ST2 isolates containing a pICE-Sepi-ST2 also have a mutated sdrG gene. Thus, all ST2 isolates have two genetic modifications that target distinct steps in the hemostatic pathway. SdrG, which inhibits coagulation, is inactivated, and SesY, which inhibits fibrin, is introduced. These findings suggest that the hemostasis pathway is a strategic target for ST2 S. epidermidis bloodstream pathogenesis.IMPORTANCEThis study uncovers a new virulence mechanism in Staphylococcus epidermidis ST2 bloodstream isolates. We identify a mobile genetic element (MGE) characteristic of an integrated conjugated element (ICE). pICE-Sepi-ST2 carries the genetic information needed to produce a cell wall-anchored (CWA) protein called SesY. The results indicate that SesY binds to plasminogen (Plg) and plasmin (Pln) and inhibits Pln’s degradation of fibrin clots. Genetic analysis showed that all ST2 bloodstream isolates can express the plasmin inhibitor SesY and carry a mutation in the SdrG gene, resulting in the expression of inactive SdrG. Thus, we describe a molecular pathway targeting the coagulation pathway that may be required for S. epidermidis ST2 to cause bloodstream infections.